The Cultivation of Students' Logical Thinking in Chinese Primary School Mathematics Education - Mingjing, Huang; Yidi, Feng (Universitas Muhammadiyah Mataram, 2022)
Mathematics is a subject that studies concepts such as quantity, structure and space and their changes. From a certain point of view, it belongs to a kind of formal science. Mathematics develops from counting, calculating, measuring, and observing the shape and motion of objects using abstraction and logical reasoning. Logical thinking ability refers to the ability to analyze, generalize, synthesize and judge reasoning problems, which is mainly manifested in mathematics. Therefore, mathematics education plays an important role in the cultivation of primary school students' logical thinking. The goal of this paper is to understand how mathematics education in primary schools in China fosters logical thinking in students. This paper adopts the method of qualitative research and conducts research through literature research and comparative analysis. The author will analyse the aspects of educational mode, educational content and educational tools, etc. To explore how Chinese primary school mathematics curriculum develops students' logical think. Logic training is a long-term process. Therefore, China has done very detailed training in primary school students' logical thinking. This is especially reflected in primary school mathematics education, including mathematics classroom teaching content, teaching methods and teaching strategies.